Frequency of adverse side effects of doxorubicin and factors influencing patients' experience - Perić, Ivana (Education and Research in Health Sciences, 2025)
Introduction: According to the definition by the US National Institute for Occupational Safety and Health, cytostatics are a group of drugs classified as hazardous medications.Cytostatics are used in cancer chemotherapy, and doxorubicin is considered as one of the most effective cytostatics in breast cancer chemotherapy in women. In addition to its effect on destroying malignant cells, doxorubicin chemotherapy also causes damage to healthy cells, leading to a range of side effects.Objective: To examine the frequency of side effects experienced by patients during doxorubicin chemotherapy and the factors that influence their experience.Methodology: The study was conducted at the General Hospital in Požarevac. It included 30 female patients undergoing doxorubicin chemotherapy. The research instrument consisted of a specifically created questionnaire for this study.Results: The most frequentside effect of the drug that was reported is alopecia. Most patients are satisfied with the information received about doxorubicin, but only 10% regularly receive information update about their therapy. All patients agree that they are satisfied with the approach and communication with the nurses, around 90% highlighting the support from the nurses, while a slightly smaller percentage (twothirds) emphasizes their compassion and understanding.Conclusion: Based on the research, it is concluded that several key factors influence the experience of patients during doxorubicin therapy. The majority of patients report the significant impact of hair loss during treatment. Although patients receive adequate information and support, the side effects of treatment and their impact on daily life still pose a difficulty.Satisfaction with the work and communication of the nurses is high, still there is room for improvement in the frequency of information and materials that patients can use at home.
Keywords: cytostatics; doxorubicin; side effects; education; nurses; patient satisfaction